The Effect of Eight Weeks of Aerobic Exercise and Ferulic Acid Supplementation on the Oxidative Stress Indices of the Experimental Model of Breast Cancer in Mice - Maryam Pira; Khosro Jalali-Dehkordi; Farzaneh Taghian; Rozita Nasiri (مجله پژوهش در علوم توانبخشی, 2021)
Introduction: Ferulic acid is a phenolic compound found in various cereals and studies show that this compound has antioxidant, anti-apoptotic, and differentiating effects on nerve cells. The aim of this study was to evaluate the effect of eight weeks of aerobic exercise and ferulic acid consumption on the oxidative stress indices of the experimental model of breast cancer in mice.Materials and Methods: In this experimental experiment, 30 female Balb/C mice weighing 220-250 g with breast cancer were divided into 1) control+, 2) control-, 3) ferulic acid supplementation, 4) exercise, and 5) exercise + ferulic acid supplements. By induction of breast cancer 14 days after injection of 1 × 106 T14 cells subcutaneously in the groin of four-week-old female Balb/C mice, a sample model of breast cancer in mice was obtained. For eight weeks, groups 3 and 4 daily consumed a dose of 200 microliters by gavage, and groups 4 and 5 performed aerobic exercise five days a week. One-way analysis of variance (ANOVA) with Tukey post-hoc test was used to analyze the findings at significance level of 0.05.Results: Eight weeks of ferulic acid supplementation significantly increased the amount of superoxide dismutase (SOD) (P ≤ 0.01). Catalase (CAT) levels increased significantly after eight weeks of aerobic exercise with ferulic acid supplementation and ferulic acid supplementation alone (P ≤ 0.01). Moreover, aerobic exercise with ferulic acid supplementation and ferulic acid consumption alone significantly reduced malondialdehyde (MDA) (P ≤ 0.01).Conclusion: It seems that aerobic exercise with ferulic acid supplementation has more favorable effects on improving SOD, CAT, and MDA levels in breast cancer than any other alone. Therefore, the use of ferulic acid with aerobic exercise is recommended in cases of breast cancer.